Temporal and spatial dynamics of spinal sensorimotor processing in an intersegmental cutaneous nociceptive reflex - White, Jason M. (J Neurophysiol, 2019)
The cutaneus trunci muscle (CTM) reflex produces a skin “shrug” in response to pinch on a rat’s back through a three-part neural circuit: 1) A-fiber and C-fiber afferents in segmental dorsal cutaneous nerves (DCNs) from lumbar to cervical levels, 2) ascending propriospinal interneurons, and 3) the CTM motoneuron pool located at the cervicothoracic junction. We recorded neurograms from a CTM nerve branch in response to electrical stimulation. The pulse trains were delivered at multiple DCNs (T(6)–L(1)), on both sides of the midline, at two stimulus strengths (0.5 or 5 mA, to activate Aδ fibers or Aδ and C fibers, respectively) and four stimulation frequencies (1, 2, 5, or 10 Hz) for 20 s. We quantified both the temporal dynamics (i.e., latency, sensitization, habituation, and frequency dependence) and the spatial dynamics (spinal level) of the reflex. The evoked responses were time-windowed into Early, Mid, Late, and Ongoing phases, of which the Mid phase, between the Early (Aδ fiber mediated) and Late (C fiber mediated) phases, has not been previously identified. All phases of the response varied with stimulus strength, frequency, history, and DCN level/side stimulated. In addition, we observed nociceptive characteristics like C fiber-mediated sensitization (wind-up) and habituation. Finally, the range of latencies in the ipsilateral responses were not very large rostrocaudally, suggesting a myelinated neural path within the ipsilateral spinal cord for at least the A fiber-mediated Early-phase response. Overall, these results demonstrate that the CTM reflex shares the temporal dynamics in other nociceptive reflexes and exhibits spatial (segmental and lateral) dynamics not seen in those reflexes. NEW & NOTEWORTHY We have physiologically studied an intersegmental reflex exploring detailed temporal, stimulus strength-based, stimulation history-dependent, lateral and segmental quantification of the reflex responses to cutaneous nociceptive stimulations. We found several physiological features in this reflex pathway, e.g., wind-up, latency changes, and somatotopic differences. These physiological observations allow us to understand how the anatomy of this reflex may be organized. We have also identified a new phase of this reflex, termed the “mid” response.